2006
DOI: 10.1111/j.1600-0668.2006.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characterization of indoor/outdoor particulate matter in two residential houses in Oslo, Norway: measurements overview and physical properties - URBAN-AEROSOL Project

Abstract: Indoor/outdoor measurements have been performed in the Oslo metropolitan area during summer and winter periods (2002-2003) at two different residential houses. The objective of the measurement study was to characterize, physically and chemically, the particulate matter (PM) and gaseous pollutants associated with actual human exposure in the selected places, and their indoor/outdoor relationship. In this paper, we focus on the PM measurements and examine the relationship between the indoor and outdoor PM concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
(27 reference statements)
2
24
0
1
Order By: Relevance
“…The average outdoor particle concentrations during different seasons were from 8 to 15 μg/m 3 for PM 10 and 4 to 10 μg/m 3 for PM 2.5 (Table 2). They mainly correspond to relatively good air quality and are similar to those observed in earlier studies in clean rural and suburban areas as well as in Kuopio (Monn et al, 1997;Jones et al, 2000;Sillanpää et al, 2003;Lazaridis et al, 2006;Portin et al, 2012) and are generally lower than those observed in European urban environments (Gotschi et al, 2002;Komarnicki, 2005;Pennanen et al, 2007;Diapouli et al, 2011). The highest concentrations were observed during the summer campaign when the air quality was affected by wildfires burning in Russia (Portin et al, 2012).…”
Section: Size Segregated Particle Concentrationssupporting
confidence: 73%
See 1 more Smart Citation
“…The average outdoor particle concentrations during different seasons were from 8 to 15 μg/m 3 for PM 10 and 4 to 10 μg/m 3 for PM 2.5 (Table 2). They mainly correspond to relatively good air quality and are similar to those observed in earlier studies in clean rural and suburban areas as well as in Kuopio (Monn et al, 1997;Jones et al, 2000;Sillanpää et al, 2003;Lazaridis et al, 2006;Portin et al, 2012) and are generally lower than those observed in European urban environments (Gotschi et al, 2002;Komarnicki, 2005;Pennanen et al, 2007;Diapouli et al, 2011). The highest concentrations were observed during the summer campaign when the air quality was affected by wildfires burning in Russia (Portin et al, 2012).…”
Section: Size Segregated Particle Concentrationssupporting
confidence: 73%
“…These correspond to 76-122% of the outdoor concentrations and are generally among the lowest concentrations usually observed in indoor air studies (Monn et al, 1997;Gotschi et al, 2002;Lazaridis et al, 2006;Chen and Hildemann, 2009) which are a result of low outdoor concentrations but also indicate the relatively small impact from indoor sources. In addition, the filtration of the house intake air may decrease the contribution of coarse particles from outdoor aerosols when compared to naturally ventilated buildings.…”
Section: Size Segregated Particle Concentrationsmentioning
confidence: 99%
“…Moreover, there are measurements in the literature to provide a reasonable basis for estimating the ratio, at least for some types of dwellings. In the absence of significant indoor sources, indoor and outdoor PM 2.5 levels are generally observed to track each other fairly closely over time with indoor concentrations lower than outdoors [44,45]. Relatively few studies have attempted to quantify explicitly the contribution of ambient PM 2.5 to indoor concentrations [46].…”
Section: Discussionmentioning
confidence: 99%
“…Sources of indoor ambient particles are not only from outdoor contributions, but also from indoor sources such as smoking, cooking, combustion, indoor resuspension of dusts by human activities, and transformation processes [43,44]. To reduce errors in the measurement and bias of the exposureeffect relationship, we repeatedly measured personal exposure instead of using outdoor or indoor area monitoring data as an exposure estimate.…”
Section: Discussionmentioning
confidence: 99%